2015
DOI: 10.1111/acfi.12098
|View full text |Cite
|
Sign up to set email alerts
|

Investor mood and the determinants of stock prices: an experimental analysis

Abstract: We examine, in a controlled experimental setting, whether changes in investor mood cause changes in the determinants of stock prices. Our results show that a deterioration in mood, reflected in the negative dimensions of mood state, increases the level of risk aversion in male, but not female, investors. We find no evidence to suggest that a change in mood impacts on investors' forecasts of future earnings or future cash flows. By establishing the causal impact of a change in mood on risk aversion, our study p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 84 publications
2
14
0
Order By: Relevance
“…These different results need to have further projects conducted and completed to validate more accurate conclusions.Furthermore, the result supported the hypothesis H4.1, in which positive mood significantly affected investment performance. Basically, these consequences are comparable and consistent with research conducted byHarding and He (2015),Shu (2010), andGrable and Roszkowski (2008). Interestingly, investors who feel cheerful, happy, relaxed, delighted or excited have good results including the return rate investors achieved as required and is higher than previous results.…”
supporting
confidence: 84%
See 1 more Smart Citation
“…These different results need to have further projects conducted and completed to validate more accurate conclusions.Furthermore, the result supported the hypothesis H4.1, in which positive mood significantly affected investment performance. Basically, these consequences are comparable and consistent with research conducted byHarding and He (2015),Shu (2010), andGrable and Roszkowski (2008). Interestingly, investors who feel cheerful, happy, relaxed, delighted or excited have good results including the return rate investors achieved as required and is higher than previous results.…”
supporting
confidence: 84%
“…Particularly, investors are recommended to pay attention to personality traits and moods that contribute to influence on investment performance because Schwager (1993, p.49) emphasizes that "trading is emotion" and "it is mass psychology, greed and fear". Recent financial research has also shown that investors' personality is correlated to stock market investment (Cooper et al, 2000;Gherzi et al, 2014;Rizvi & Fatima, 2015) and mood takes a vital position in financial investment, even in decisions under risk and/or uncertainty (Loewenstein et al, 2001;Shu, 2010;Fenton-O'Creevy et al, 2011;Harding & He, 2015;Lepori, 2015). Apparently, there is an effect of personality traits or moods on investment performance.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, there is a relative scarcity of research employing alternative methodologies to quantitative, such as surveys and experiments (Benson et al ., ). Noteworthy exceptions are recent studies on the behavioural underpinnings of individual investor beliefs and preferences (Tourani‐Rad and Kirkby, ; Gerrans et al ., ; Harding and He, ). We add to this emerging stream of literature by conducting a field study to examine how individual investors update their beliefs (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, an extensive literature argued that moods and emotions significantly affect individuals" financial decision-making process (Damasio, 1994;Loewenstein et al, 2001;Harding and He, 2016). Nevertheless, there is no agreement on the nature of this behavioural relationship.…”
Section: Literature Reviewmentioning
confidence: 99%